Improving Student Learning Outcomes Through The Think Pair Share (TPS) Learning Method - Sarah Wassar; Kezia Verena (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
The goal of this study is to ascertain whether using learning model Think Pair Share (TPS) improves student interest and science learning outcomes. Classroom action research (PTK) is the term for this kind of study. Learning outcomes in science and interest rose by 14.82%. According to the questionnaire results for each cycle, the average percentage of student interest increased from 73.43% in the first cycle to 79.82% in Cycle II. Ten students, or 35.71% of the total, have finished at pre-cycles. One student's percentage of mastery rises to 60.71%, or 17 finished students, after completing a cycle action. With an average score of 84.46, the percentage of students who experience mastery has then increased to 100% in cycle two.